Necessary conditions of extremum, penalty functions and regularity - Pshenichny , B. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
General conditions for regularity of a point relative to a system of nonlinear equations are stated. It is shown that if the regularity conditions are fulfilled, the general problem of mathematical programming could be reduced to the minimization of a nonsmooth penalty function and the necessary conditions for the extremum could be stated in the most general form.